Erratum: WANG, H.Q., LI, K. & LIU, X.W. (2012) A taxonomic study on the species of the genus Phlugiolopsis Zeuner (Orthoptera, Tettigoniidae, Meconematinae). Zootaxa, 3332, 27–48. - Wang, H. Q.; Li, K.; Liu, X. W. (Zootaxa, 2012)
(Erratum)